2008
DOI: 10.2511/rpsd.33.1-2.3
|View full text |Cite
|
Sign up to set email alerts
|

Teaching Elementary Students with Multiple Disabilities to Participate in Shared Stories

Abstract: Literacy may be one of the most important instructional areas for enhancing quality of life for all students. One way to promote literacy skills is through engaging students in the shared reading of a story. In this study, methods for planning and implementing shared stories for three students with multiple disabilities was evaluated via a multiple probe design across participants. Because the students had few consistent responses and complex physical challenges, a team planned the literacy participation using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
99
0
6

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 92 publications
(110 citation statements)
references
References 21 publications
5
99
0
6
Order By: Relevance
“…A review of research studies on UDL in the classroom (Rao, Ok, & Bryant, 2014) found that researchers have applied UDL to various levels of curriculum and instruction. Researchers have examined how UDL can be applied to teacher-developed lessons and curricula (Browder, Mims, Spooner, Ahlgrim-Delzell, & Lee, 2008;Dymond et al, 2006;King-Sears et al, 2015). Several studies have examined academic outcomes and engagement with UDL-based digital learning environments (Coyne, Pisha, Dalton, Zeph, & Smith, 2012;Dalton, Proctor, Uccelli, Mo, & Snow, 2011;Hall, Cohen, Vue, & Ganley, 2015;Marino et al, 2014;Rappolt-Schlichtmann et al, 2013).…”
Section: Background On Udlmentioning
confidence: 99%
“…A review of research studies on UDL in the classroom (Rao, Ok, & Bryant, 2014) found that researchers have applied UDL to various levels of curriculum and instruction. Researchers have examined how UDL can be applied to teacher-developed lessons and curricula (Browder, Mims, Spooner, Ahlgrim-Delzell, & Lee, 2008;Dymond et al, 2006;King-Sears et al, 2015). Several studies have examined academic outcomes and engagement with UDL-based digital learning environments (Coyne, Pisha, Dalton, Zeph, & Smith, 2012;Dalton, Proctor, Uccelli, Mo, & Snow, 2011;Hall, Cohen, Vue, & Ganley, 2015;Marino et al, 2014;Rappolt-Schlichtmann et al, 2013).…”
Section: Background On Udlmentioning
confidence: 99%
“…Koppenhaver, Erickson, and Skotko (2001) found girls with Rett syndrome made gains in early symbolic communication when they participated in shared story reading with their mothers. In addition, Browder, Mims, Spooner, Ahlgrim-Delzell, and Lee (2008) found shared story reading increased the independent responses of three students with profound disabilities who had previously been unresponsive during reading instruction. Mims, Browder, Baker, Lee, and Spooner (2009) found shared story reading promoted listening comprehension for two elementary students with significant intellectual disability and visual impairments.…”
mentioning
confidence: 96%
“…Additionally, many chained tasks, such as completing the steps to composing a paragraph, completing a long division problem, or participating in an inquiry lesson can be taught using a task analysis of the steps. Specifically in ELA, current research supports the use of read alouds and task analytic instruction to increase foundational literacy skills as well as comprehension (e.g., Browder, Mims, et al, 2008). In math.…”
Section: Summary Oe Academic Instruction In Ela Math and Sciencementioning
confidence: 57%
“…Blyden (1988) found that shared book readings with adaptations (e.g., large print, pictures, sign language) increased attention skills, receptive and expressive language skills, social interaction, and active participation for the students witb multiple disabilities. Browder, Mims, Spooner, Ahlgrim-Delzell, and Lee (2008) used grade-level read alouds in an elementary classroom witb tbree students with severe intellectual and physical disabilities. The planning team used components of UDL to develop ways to adapt tbe read alouds.…”
Section: Literacy Instruction Through Read Aloudsmentioning
confidence: 99%